Denitrification of a high nitrate containing industrial wastewater in a suspended growth system. - Parco, Gerardo F. (Philippine Engineering Journal)
The aim of this study is to evaluate the possibility of direct denitrification of concentrated wastewater, NO3-N concentrations of 1200-1760 mg/li. Special consideration was given to inhibition effects due to highly concentrated nature of the wastewater. Based on this study a design for full scale application was made. Chemostat trials were performed employing a 2 day residence time and batch trials were carried out to determine kinetic parameters ks and us. Sludge from an existing oxidation ditch plant was used as innoculant. Initial results in the chemostat trials showed inhibition occurring at 30 percent dilution of the wastewater. At high dilution ratios, equivalent to 60 percent dilution, washout occurred. Various trials were used to determine the inhibiting component in the wastewater. The carbon source was primarily ethylene glycol. Various interventions were investigated in order to overcome the inhibitory effect of which only dilution was seen as effective. The inhibitory effect was assumed to be due to the effect of the carbon source. Both the mono and di-ethylene glycol species were present in the wastewater of which the mono-ethylene glycol made up 80 percent of the total. The glycol effect may be seen as affecting the microbial cells by increasing the osmotic pressure. To overcome the glycol effect, it is necessary to dilute the wastewater. A two reactor system was proposed to achieve denitrification while providing a source for dilution water. The effluent from the first reactor, a denitrification reactor, was fed to an aerobic reactor where the remaining COD as glycol is oxidized and the effluent from this reactor is split and part is fed back to the denitrification reactor as dilution water and part is disposed of as final effluent. A mathematical model was proposed using both Monod and inhibition kinetics. Design charts at different dilution ratios were made from the resulting mathematical model. The results show substantial denitrification results in the two reactor system depending on the dilution ratio employed. It shows the possibility of direct denitrification by using a two reactor system while at the same time substantially decreasing the COD in the wastewater.